Analisis Kualitas Instrumen Angket Pengamalan Fikih Jinayah pada Mata Kuliah Fikih di Perguruan Tinggi - U, M. Shabir; Damopolii, Muljono (Faculty of Tarbiyah and Teacher Training, 2026)
The evaluation of Fiqh learning in higher education requires not only measuring students’ conceptual mastery but also assessing the capacity of assessment instruments to capture the dimensions of value internalization and attitudinal practice. Therefore, the quality of questionnaire instruments used to assess non-cognitive aspects plays a crucial role in determining the accuracy of evaluation outcomes. This study aims to develop and validate a questionnaire instrument to measure students’ engagement with aspects of Jinayah in the Fiqh course, ensuring it meets established standards of validity and reliability. This research employed a descriptive quantitative approach, with participants drawn from students of the Faculty of Tarbiyah and Teacher Training at UIN Alauddin Makassar. Data were collected using a closed-ended Fiqh Jinayah practice questionnaire based on a Likert scale. Data analysis focused on assessing the instruments' validity and reliability. Item validity was examined using the Pearson Product–Moment correlation, while instrument reliability was assessed using Cronbach’s Alpha coefficient, with the assistance of SPSS software. The results indicate that of 40 items tested, 36 were found valid, while 4 did not meet the validity criteria. Meanwhile, the reliability analysis yielded a Cronbach’s Alpha coefficient of 0.899, indicating very high internal consistency. These findings suggest that, overall, the Fiqh Jinayah practice questionnaire demonstrates good quality, is valid and reliable, and is therefore suitable for use as an evaluation tool to assess students’ practice in Fiqh learning at the higher education level. The instrument is expected to support a more comprehensive evaluation of learning that emphasizes the internalization of Fiqh Jinayah values.